A modified shuffled frog leaping algorithm and its application to short-term hydrothermal scheduling / Mohamad Khairul Hakimi Abdul Hady - Abdul Hady, Mohamad Khairul Hakimi (2016)
This thesis discusses the solution of short-term hydrothermal scheduling problem using modified shuffled frog-leaping algorithm, which is inspired by the behavior of a group frog to find a place that has the most food optimization technique purpose that has been develop for solving the hydrothermal scheduling problem. Short-term hydrothermal scheduling is defined as commitment and dispatching of thermal and hydro units in order to minimize the cost while fulfill the demand. Hydrothermal scheduling problem involves large, nonconvex, dynamic and nonlinear programing by observing all constraints. The most important purpose of this study is to obtain the minimum total fuel cost at thermal and the optimal generated power process for every unit hydro and thermal plant. This paper presents a modified shuffled frog leaping algorithm in order to accelerate the global search solution. This modified SFLA (MSFLA) is developed in MATLAB programming and tested on a system with three thermal unit plants and four hydro unit plants. The result shows that the MSFLA is able to provide a solution for hydrothermal scheduling problem.